Social Change in the Society of Medina: A Sociological Study of the Da'wah of the Prophet Muhammad - Syawaludin, Mohammad (Rumah Riset Publisher, 2025)
This research discusses the social changes that occurred in the society of Medina as a result of the da'wah of the Prophet Muhammad SAW, with a sociological approach. Before the arrival of the Prophet, the people of Medina experienced inter-tribal conflicts, social inequality, and a weak value system that held the community together. Through da'wah that is inclusive, gradual, and touches various aspects of life, the Prophet Muhammad succeeded in forming a new social order based on the values of monotheism, justice, and brotherhood. This study analyzes the da'wah strategy, the process of forming the Medina Charter, and the changes in the social structure that are caused, such as the realization of solidarity between people, social integration, and a government system based on Islamic values. With a qualitative approach and literature study, this study shows that the Prophet's da'wah is not only spiritual, but also has a significant impact on the social transformation of society. The results of this analysis are expected to provide a deeper understanding of the role of religion in forming a harmonious and just social order.